NILAI EDUKASI DALAM LIRIK TEMBANG DOLANAN DI SD MUHAMMADIYAH 26 SURABAYA - Rachmawati, Dian Karina; Suryadi; Ayu Pramudya , Dwiki (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2024)
Tembang dolanan is an oral literature or song intended for children as a game accompaniment. One example is the dolanan song Sunan Giri from East Java. This study aims to reveal the educational values ​​contained in the lyrics of the song. The theory used to analyze the value of education is a folklore study to find out the historical origins of the dolanan song brought by Sunan Giri at the time when it was used as a medium of da'wah for the people of Gresik. In addition, this Foklore uses the theory of Danandjaja (1991). This study uses a qualitative descriptive research design according to Faruk in (Rofifah, 2020), namely by identifying the lyrics of the Sunan Giri dolanan song and then describing them. The primary data used in this study is written data in the form of song lyrics, oral data in the form of the history of Sunan Giri from sources who are studied using deep metaphor theory (Rachmawati, 2017). The results of the study show that the lyrics of the dolanan song contain a lot of Islamic educational value. One of the concepts of deep educational value that is poured into the lyrics of dolanan songs, one example of Cublek – Cublek Suweng is the ideology of advice in finding treasure, Padhang Bulan contains the educational value of Islam as information, and Gambang Suling contains hegemonic tactics in balancing life. These meanings contained in the lyrics of the song dolanan are more comprehensive, easy to interpret and then applied to various aspects of life.